Non-linear phenomena connected with propogation of the drift waves into plasma - Khvesyuk, V.I.; Chirkov, A.Yu. (Вопросы атомной науки и техники, 2006)
Non-linear heat and particle transport and restriction of wave amplitudes are discussed. Non-linear transformation of drift wave is considered under influence of outer non-uniform static electric field.